Cryo-EM Structure of the African Swine Fever Virus - Liu, Sheng; Luo, Yuzi; Wang, Yajuan; Li, Shihua; Zhao, Zhennan; Bi, Yuhai; Sun, Junqing; Peng, Ruchao; Song, Hao; Zhu, Dongjie; Sun, Yuan; Li, Su; et al. (Cell host & microbe, 2019)
African swine fever virus (ASFV) is a large double-stranded DNA virus with an icosahedral multilayered structure. ASFV causes a lethal swine hemorrhagic disease and is currently responsible for widespread damage to the pork industry in Asia. Neither vaccines nor antivirals are available and the molecular characterization of the ASFV particle is outstanding. Here, we describe the cryogenic electron microscopy (cryo-EM) structure of the icosahedral capsid of ASFV at 4.6-Å. The ASFV particle consists of 8,280 copies of the major capsid protein p72, 60 copies of the penton protein, and at least 8,340 minor capsid proteins, of which there might be 3 different types. Like other nucleocytoplasmic large DNA viruses, the minor capsid proteins form a hexagonal network below the outer capsid shell, functioning as stabilizers by “gluing” neighboring capsomers together. Our findings provide a comprehensive molecular model of the ASFV capsid architecture that will contribute to the future development of countermeasures, including vaccines. [Display omitted] •Cryo-EM structure of the icosahedrally averaged ASFV capsid described at 4.6-Å•ASFV capsid comprises 8,280 major capsid protein p72 and 60 penton protein copies•At least three different minor proteins stabilize capsid by gluing neighboring capsomers•ASFV differs from other NCLDVs in multilayered structure and icosahedral morphology African swine fever virus (ASFV) is a large DNA virus that causes a lethal swine hemorrhagic disease and is currently responsible for widespread outbreaks in domestic pigs. Liu et al. describe the cryo-EM structure of ASFV capsid at 4.6-Å, which reveals several critical proteins and structural elements.